A representação social dos adolescentes à luz das políticas públicas no corredor da fronteira do Iguaçu em 2012 - Kniphoff, Dione (2012)
From a limited conception about these youth, government programs sought only, and not always successfully, to minimize the potential threat that youth seem to pose to society. The construction of public policies for youth coming up in the absence of an agenda that includes the issues and problems youth, and which also contemplates youth as participants in this process. Despite the expansion of the demands of the youth population, it is known that public policies for these are incipient and discontinuous in Latin America, there is still an important gap in the sense of turning government policy into effective public to youth. To this end, it becomes necessary to break with the sectorization of youth policies, to break with the utilitarian view of the condition or stigmatized youth, encourage a better relationship between civil society and youth, promoting youth participation in the construction of their citizenship. In this context, it is urgent to promote research on the social visibility and expressions yout h as a backdrop, the crisis of institutions, social conventions, concepts and explanatory theories. This study aims to provide tools that enable the understanding of social, political, economic and cultural, knowing that this understanding will promote initiatives to improve the condition of public policy development appropriate to the needs of the population children and youth in the city of Foz do Iguaçu and Santa Tereza do Oeste, understanding the corridor from the border of Iguaçu as part of the BR 277 highway, between the municipality of Cascavel and Foz do Iguacu, as a territory that requires a different view. Thus, the study sought to understand the social representation of teenagers on public policy in the corridor from the border of Iguaçu in 2011. To this end, we sought to identify and rank the children and youth public policy at the border, to verify the impact of these policies on the population served by means of qualitative research on teenagers social representation on public policy in the corridor from the border of Iguaçu in 2011 and collect data qualitative among the beneficiaries of these policies in Foz do Iguaçu and Santa Tereza do Oeste in 2011. It was observed that such policies were being driven from what youth live and the prospect of building values and attitudes to new generations. For this feat, it is important to provide the population with youth to promote interdisciplinary studies and public actions.